2018
DOI: 10.1007/s10755-018-9421-7
|View full text |Cite
|
Sign up to set email alerts
|

University Advertising and Universality in Messaging

Abstract: the impact of performance funding, in which a portion of state funding is allocated based on student outcomes, on the completion of short-term certificates, medium-term certificates, and associate degree was examined. A difference-in-differences methodology, controlling for state-and college-level variables, showed that performance funding had little effect on the rate of completion of the different degree types. But a detailed analysis found that policies in effect for more than 2 years, the proportion of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Building on Harris's work, Clayton et al (2012) observed the same five themes, but with an additional focus on community-building and belonging. In a recent study, Diel and Katsinas (2018) also found that the PSAs focused more on the student experience (social activity, campus environment, etc.) than academic achievement.…”
Section: The Meanings Of Higher Educationmentioning
confidence: 94%
“…Building on Harris's work, Clayton et al (2012) observed the same five themes, but with an additional focus on community-building and belonging. In a recent study, Diel and Katsinas (2018) also found that the PSAs focused more on the student experience (social activity, campus environment, etc.) than academic achievement.…”
Section: The Meanings Of Higher Educationmentioning
confidence: 94%
“…Fuente: Diel and Katsinas (2018) 4) En cuarto lugar, Mogaji y Yoon (2019) señalan los principales temas y subtemas clave en los mensajes de marketing de los folletos de las universidades del Reino Unido (tabla 5): la ubicación de la universidad, la variedad de cursos que se ofrecen, las instalaciones para mejorar las experiencias de los estudiantes, la credibilidad, la reputación y el esfuerzo hacia el progreso profesional de los estudiantes: 2014) explican que los estudiantes universitarios de hoy son reclutados en los sitios web con mensajes de preparación para el trabajo y no para el desarrollo intelectual o el compromiso académico (tabla 6). Es así, mucho de lo que aparece en los sitios web es una representación genérica del estilo de vida asociado con la asistencia a la universidad y no con la búsqueda del conocimiento.…”
Section: Elementos De Anuncios De Las Universidades Frecuenciaunclassified
“…Esta estrategia publicitaria basada en las emociones puede tener el efecto deseado, ya que las universidades cruzan las fronteras estatales para atraer a los estudiantes de otras regiones. No obstante, las universidades públicas que se centran en el atractivo emocional pueden perder la oportunidad de presentarse como instituciones generadoras de valor económico y capital social (Diel y Katsinas, 2018). Del análisis de campañas publicitarias de educación superior exhibidas en Norteamérica, Europa y Japón se concluye que los estudiantes constituyen el elemento más destacado y central en la mayoría de los anuncios.…”
Section: Los Anuncios Publicitarios En La Educación Superiorunclassified